Comfortable high street in CBD of Johor Bahru - Sinaei, Amir (2013)
High street has significant role in urban context. It is not only a way for passing to get another place, but it can also clarify social and cultural aspects of the society in each city. but these days, it is because of over using of vehicles especially private cars in central business district (CBD) of our cities the most places dedicated to cars, the wide street for decline traffic, a huge space for parking place and so on and so forth. Consequently, there is not any pull factor for people to walk along and enjoy of quality of space in high street. Therefore, Comfortability is both physical and mental attributes to enhance the quality of high street. Thus, this research examined and assessed comfortable high street as a kind of re-imagination for today's high street situation to make it a pleasant and enjoyable place. Case study method is selected by the supporting of literature review, site observation and the questionnaire survey to investigate physical and mental aspects of comfortability in Jalan Wong Ah Fook in CBD of Johor Bahru as one of the most important high streets in this city. Jalan Wong Ah Fook with both highlight historical background and modern high-rise building has specific cultural and social identity. Eventually in this survey comfortability in three important part of Jalan Wong Ah Fook which included public transit (pedestrian, private vehicles and public transportation), public space as a significant place to attract large number of people in the high street and last but not least factor is activities which have important role to give comfortable feeling to street users. In summary, comfortable feeling is important for people who use the high street to have better connection with urban context.